Biomechanical analyses of different serve and groundstroke techniques in tennis: A systematic scoping review - Lambrich, J.; Muehlbauer, T. (PLOS ONE, 2023)
This systematic scoping review aims to summarize findings regarding kinetic, kinematic, and electromyographic analyses of different characteristics (i.e., type/direction and stance style) of the tennis serve and groundstroke. A systematic search of the literature was performed on the databases PubMed, Web of Science, and SportDiscus from their inception date till May 2023. A descriptive analysis of results was conducted. The literature search identified a total of N = 899 records, 23 of which met the inclusion criteria and were analysed in this review. A total of 229 participants aged 18 to 62 years participated in the studies. The studies revealed varying results, ranging from significantly lower/higher values to no significant differences between serve/groundstroke characteristics. These inconsistent results may most likely be attributed to discrepancies in the methodological approach such as players` age (18-62 years), sex (i.e., men only or both sexes), and performance level (i.e., recreational, intermediate, or advanced) as well as the applied measurement devices (i.e., force plate or pressure-detecting insoles; motion capture system, high-speed video recordings, or IMU sensors) and used outcomes (i.e., measured or estimated force etc.). Future research is needed to provide a comprehensive biomechanical analysis of different serve/groundstroke characteristics. Specifically, it is recommended to compare different tennis serve and groundstroke types/directions and stance styles in female and male age-matched players with diverging performance levels (i.e., recreational, intermediate, advanced) using combined (i.e., kinetic, kinematic, and electromyographic) biomechanical analysis.